Kedudukan Al-Qur`an Perspektif Nahdlatul Ulama dan Aplikasinya dalam Bahṡul Masâ`il NU - Hilmy Pratomo (Syariati: Jurnal Studi Al-Qur'an dan Hukum, 2019)
Nahdlatul Ulama (NU) is an Islamic religious organization in Indonesia. As are ligious organization, NU has a fatwa institution in the form of bahṡul masâ`il which functions to respond to various socio-religious. In responding to this problem, NU has a unique dynamic in interacting with the Qur'an as the main guideline of Muslims. This paper tries to answer several problems. First, how does NU view the Qur'an. Second, what is the application in bahṡul masâ`il. The resultsof the study it can be seen that formally NU views the position of the Qur'an asabove any religious text. From the 1st Congress of 1926 to the Congress of XXXIIIin 2015, there were 536 issues, of which 89 problems were answered with the Qur'an.